Information culture and cyberculture in the context of modern society development - F. P. Vlasenko; Ye. V. Levcheniuk (Ukrainian Cultural Studies, 2019)
Goal. To carry out socio-philosophical conceptualization of the phenomenon of information culture and cyberculture as the newest factors that determine the development of modern society and is characterized by intensification of processes of informatization and technologization. Theoretical basis. The authors have proved that the concepts of information culture and cyberculture are united in the sense of theoretical generalizations about understanding the essence of modern society (mass, virtual, global, information) and so on. It is substantiated that the main condition and consequence of the development of modern society is the emergence of information culture and cyberculture, which serve as the unity of value models of technical, information and technological levels of civilization, which simultaneously forms a new type of person, which is realized in two dimensions – real (physical, social) and virtual. Scientific novelty. It is substantiated that modern society is in a state of radical large-scale, systemic transformations, the consequence of which is a new stage of development of the relation "man – world", "man – society", "man – man". According to the authors, the determining factor is the development of information culture and cyberculture, which characterize the latest achievements in the development of modern science, technology, education. Conclusions. Progressive achievements of the technosphere of the late 20-th – early 21-st century created new conditions for the development of the society and a man. These advances have both complicated and simplified social connections and relationships. This is how e-economy, e-education, e-government, e-tourism, and others have come into being and evolve. At the same time, culture is gaining a new dimension of development. It is transferred to the sphere of the Internet, network communities and is characterized as an information culture, cyberculture, forming a qualitatively new outlook with relevant values, norms, social roles and behaviors of modern man.